PENGARUH PENGGUNAAN CAMPUR KODE DALAM PEMBELAJARAN BAHASA INDONESIA PADA SISWA SMPN 7 WOJA DOMPU - Adiprasetio Prabowo (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study explores the use of code-mixing in Indonesian language learning used in the classroom of SMPN 7 Woja Dompu. The design of the study is a descriptive qualitative method that assigned students and teachers in SMPN 7 Woja.  Data were collected using documentation, interviews, and translations. This results of this study show Indonesian language learning in is conducted using code-mixing between Bahasa Indonesia and local language in terms of words, phrases, and clauses. Mixed-shaped code words occur in total  95 words, phrases shaped mixing 107, and code-mixing clause shaped 43. The use of code-mixing that dominate in this research is mixed in the form of code phrases. The use of code-mixing in the learning affects teachers to facilitate learning, but students accept the code-mixing as their usual daily interactions.